DIGITAL CONSUMER PROTECTION FROM THE PERSPECTIVE OF CONSUMER PROTECTION LAW (INTERNATIONAL SEMINAR, 2025)
The development of digital technology has expanded the scope of transactions in society through e-commerce, digital financial services, and online applications. These changes have not only provided convenience, but also given rise to new forms of vulnerability such as misuse of personal data, cyber fraud, and information imbalance between businesses and consumers (OECD, 20211; UNCTAD, 20202). This study examines how Indonesia's legal framework, including the UUPK, ITE Law, and PDP Law, responds to these phenomena using a normative legal research approach (Marzuki, 20173). The findings show that although the basis for protection is available, its effectiveness is still limited by low digital literacy, regulatory disharmony, and weak supervision and law enforcement (BPKN RI, 2021)4. This study emphasises the need for harmonisation of regulations, increased digital education for consumers, and optimisation of electronic dispute resolution mechanisms.